Объяснение:
1)
х²+9х+20<0 ; D=√(81-80)=1
Корни:
х₁=-4.
х₂=-5.
(х+4)(х+5)<0
( -)
(-5)(-4)
х∈(-5;-4)
2)
х²-2х-3<0
х₁=3 ; х₂=-1 . (можно найти по теореме ВИЕТА).
(х-3)(х+1)<0
(-)
(-1)(3)
х∈(-1 ;3).
3)
х²-7х+12<0
х₁₂=(7±√(49-48))/2=(7±1)/2.
х₁=(7+1)/2=4
х₂=(7-1)/2=3
(х-4)(х-3)<0
(3)(4)
х∈(3 ;4).
4)
х²-6х-27<0
х₁₂=3±√(9+27)=3±6
х₁=9. х₂=-3.
(х-9)(х+3)<0
(- 3)(9)
х∈(- 3 ;9).
5)
х²-17+72<0
х₁₂=(17±√(289-288))/2=(17±1)/2.
х₁=(17+1)/2=9.
х₂=(17-1)/2=8.
(х-9)(х-8)<0.
(8)(9)
х∈(8;9).
Объяснение:
1)
х²+9х+20<0 ; D=√(81-80)=1
Корни:
х₁=-4.
х₂=-5.
(х+4)(х+5)<0
( -)
(-5)(-4)
х∈(-5;-4)
2)
х²-2х-3<0
Корни:
х₁=3 ; х₂=-1 . (можно найти по теореме ВИЕТА).
(х-3)(х+1)<0
(-)
(-1)(3)
х∈(-1 ;3).
3)
х²-7х+12<0
х₁₂=(7±√(49-48))/2=(7±1)/2.
х₁=(7+1)/2=4
х₂=(7-1)/2=3
(х-4)(х-3)<0
(3)(4)
х∈(3 ;4).
4)
х²-6х-27<0
х₁₂=3±√(9+27)=3±6
х₁=9. х₂=-3.
(х-9)(х+3)<0
(- 3)(9)
х∈(- 3 ;9).
5)
х²-17+72<0
х₁₂=(17±√(289-288))/2=(17±1)/2.
х₁=(17+1)/2=9.
х₂=(17-1)/2=8.
(х-9)(х-8)<0.
(8)(9)
х∈(8;9).